2020
DOI: 10.1002/mnfr.201901037
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Hydrolysis of Curcumin Conjugates by β‐Glucuronidase: Detection of Complex Conjugates in Plasma

Abstract: Scope The diphenol curcumin from turmeric is rapidly metabolized into phase II conjugates following oral administration, resulting in negligible plasma concentration of the free compound, which is considered the bioactive form. Total plasma concentration of curcumin is often quantified after treatment with β‐glucuronidase to hydrolyze curcumin‐glucuronide, the most abundant conjugate in vivo. The efficiency of enzymatic hydrolysis has not been tested. Methods and results Using liquid chromatography–mass spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
(71 reference statements)
1
8
0
Order By: Relevance
“…Also, as NC plasma concentration decreased, the NC content in tissues increased and it was shown that the distribution of NC in tissues is higher than C. It has been shown that C can be metabolized in the kidney by the β-glucuronidase and sulfatase enzymes. 32 , 33 Therefore, complete clearance from plasma 72 h after the last dose of NC and C in the present study indicates complete urinary C and NC excretion.…”
Section: Discussionsupporting
confidence: 61%
“…Also, as NC plasma concentration decreased, the NC content in tissues increased and it was shown that the distribution of NC in tissues is higher than C. It has been shown that C can be metabolized in the kidney by the β-glucuronidase and sulfatase enzymes. 32 , 33 Therefore, complete clearance from plasma 72 h after the last dose of NC and C in the present study indicates complete urinary C and NC excretion.…”
Section: Discussionsupporting
confidence: 61%
“…As the suitable conjugate standards of polar phenolics are rarely commercially available for analysis, the majority of studies on their bioavailability repeatedly treat biofluid samples with glucuronidase/sulfatase enzymes for the subsequent quantification of the released aglycones [ 38 ]. To date, a few studies have questioned the efficacy of enzymatic hydrolysis for the reliable quantification of glucuronidated and sulfated metabolites of polar phenolics in biofluids [ 24 , 29 , 39 ]. According to Quifer-Rada et al [ 29 ], enzymatic hydrolysis negatively affected the recovery of the precursor and free-form polar phenolics present in human urine samples.…”
Section: Resultsmentioning
confidence: 99%
“…are often pre-treated with deconjugating enzymes to liberate the aglycone prior to pharmacokinetic analyses (51,58). This practice, however, is not always well documented or characterized, nor are the clinical implications of low in vivo, bioactive aglycones always considered (60,67).…”
Section: Pharmacokinetic Analysesmentioning
confidence: 99%
“…Indeed, in the case of curcuminoids, these conjugates can persist in the circulation for over 24 h (e.g., 10% of administered curcuminoids, independent of dose) ( 61 ), due in part to enterohepatic recirculation ( Figure 4A ) ( 60 65 ). For this reason, and because glucuronide conjugates are difficult to analyze ( 66 ), serum samples for curcuminoids and other botanicals are often pre-treated with deconjugating enzymes to liberate the aglycone prior to pharmacokinetic analyses ( 51 , 58 ). This practice, however, is not always well documented or characterized, nor are the clinical implications of low in vivo , bioactive aglycones always considered ( 60 , 67 ).…”
Section: Choice Of Botanical Product For Studymentioning
confidence: 99%
See 1 more Smart Citation